Non-synchronic modernity: social acceleration, de-temporalization and alienation: an interview with Hartmut Rosa - Tziminadis, João Lucas Faco (FCL-UNESP Laboratório Editorial, 2018)
The scope of this interview is to present the social experiences and the analytical categories which comprise Hartmut Rosa’s theory of social acceleration. At the outset, the questions lead the author to recall the reasons that lead to his interest in the problem of time in the present modernity, as well as the intellectual path that guided him to such an interest. The consequences of what Rosa diagnoses as a society of de-synchronized and de-temporalized acceleration are exposed and subsequently a new interpretation of the concept of alienation is proposed. Through his claim of being a successor to the school of critical social theory, Rosa also indicates the rough outlines of his critical model’s normative referential, examining the temporal maxims that make up the modern ideal of a good life.